PUBLIC DEBT SIZE IN THE EU AND POSSIBLE WAYS OF LOWERING IT BY RESTRUCTURING - Stanislav Saroch; Olga Francova (European Scientific Journal, ESJ, 2015)
The debt problem in the eurozone cannot be avoided or hoped away. The article examines different opportunities of dealing with the debt burden. There are many options how to address the debt problem. Due to dramatic circumstances a number of modifications to the original rules of the SGP such as the Six-Pack, Two-Pack and Fiscal compact became politically acceptable. However, budget stabilization cannot work for a long time in the southern EU countries being permanently in recession. There are several ways how to lower the debt burden - higher inflation, various types of state bankruptcies, federalization of Europe and takeover of the debt by a common fiscal authority or an institutional solution that requires only minimal adaptation of the existing institutional structure of the EU. The latter one being a permanent "burial" of the excessive part of current debt on the balance sheet of the ECB. Under certain conditions it is possible to design this solution as non-inflationary and by exclusion of the risk of future moral hazard in public debt incensement. The main objective of the authors is to describe possible ways to reduce debt burden building on the overview of empirical and comparative analyses available in international literature. The authors come to the conclusion that new framework for dealing with debt burden will be necessary in order to eliminate persisting obstacle hindering economic growth. The most feasible solution being the one put forward by Paris and Wyplosz. Its main asset lies in the fact that the transfer of debt burden is limited to the future generations of one country. Thus the political sensitivity of higher extent of risk-sharing among eurozone countries and lack of willingness to accept bolder solutions in this respect is overcome. All alternatives mentioned in the text remain highly complex which will make it difficult for national policy makers to obtain support for adoption of such measures among the EU citizens at individual country level.